PERFORMANCE OF STARTER PHASE NATIVE CHICKENS FEED WITH SUBSTITUTION OF WASTE FLOUR SUBSTITUTION WITH GARDEN FISH EXTRACT - Soraya Faradilla; Syamsuddin; Rosa Ure Inadai Mangun Illodo; Rafly; Sri Wahyuni (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Feeding chickens aims to meet nutritional needs, to get fast chicken growth and high productivity, quality feed is needed. Snakehead fish is a freshwater fish that contains high nutrients and has the potential to be used as a good source of protein for Ulu village chickens. This research aims to determine the performance of Ulu chickens given snakehead fish (Channa Striata) waste extract flour in feed. This research method used a Completely Randomized Design (CRD) with a total of 100 Ulu village chickens with 4 treatments and 5 replications, each replication consisting of 5 broiler chickens. Each treatment in this study was 100% Commercial Feed; Commercial Feed 96 + 4% Snakehead fish waste meal; Commercial Feed 92% + 8% Snakehead fish waste meal, Commercial Feed 88%+ 12% Snakehead fish waste meal. The parameters observed were feed consumption, body weight gain, and Feed Conversion Ratio (FCR). The results of the research showed that the performance of Ulu chickens by providing snakehead fish extract waste flour in their feed had a positive influence on the performance of Kampung Ulu chickens. The conclusion of this research is that the addition of 4% snakehead fish waste extract flour (P1) is the best treatment in terms of improving performance.